2016
DOI: 10.14336/ad.2016.0505
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Flavonoids and Catechols as Hif1 and Nrf2 Protein Stabilizers - Implications for Parkinson’s Disease

Abstract: Flavonoids are known to trigger the intrinsic genetic adaptive programs to hypoxic or oxidative stress via estrogen receptor engagement or upstream kinase activation. To reveal specific structural requirements for direct stabilization of the transcription factors responsible for triggering the antihypoxic and antioxidant programs, we studied flavones, isoflavones and catechols including dihydroxybenzoate, didox, levodopa, and nordihydroguaiaretic acid (NDGA), using novel luciferase-based reporters specific for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…In addition, Erler et al and Reynaud et al showed that LOX expression was increased by HIF‐1α in the intratumoral hypoxic condition, and resulted in distant metastasis or bone metastasis. In the current study, comprehensive analysis using a large HCC transcriptome matrix showed that high LOX expression correlates with the expression of HIF‐1α and the hypoxia pathway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Erler et al and Reynaud et al showed that LOX expression was increased by HIF‐1α in the intratumoral hypoxic condition, and resulted in distant metastasis or bone metastasis. In the current study, comprehensive analysis using a large HCC transcriptome matrix showed that high LOX expression correlates with the expression of HIF‐1α and the hypoxia pathway.…”
Section: Discussionmentioning
confidence: 99%
“…This result may suggest that early recurrence mainly occurred from IM recurrence. On the other hands, LOX expression in the background liver may influence tumorigenesis by MC and develop the late recurrence.In addition, Erler et al and Reynaud et al33,[40][41][42][43] showed that LOX expression was increased by HIF-1α in the intratumoral hypoxic condition, and resulted in distant metastasis or bone metastasis. In the current study, comprehensive analysis using a large HCC transcriptome matrix showed that high LOX expression correlates with the expression of HIF-1α and the hypoxia pathway.…”
mentioning
confidence: 99%
“…Nuclear factor-erythroid-2-related factor 2 (Nrf2)/antioxidant response element (ARE) antioxidant pathway is the most important endogenous antioxidant signaling pathway discovered so far [19,20]. Many antioxidants, such as flavonoids, polyphenols, and carotenoids, can exert antioxidant effects by activating this pathway [21][22][23]. However, it still remains unknown whether floridoside can also activate such pathway.…”
Section: Introductionmentioning
confidence: 99%
“…The activity of Nrf2 is primarily regulated via its interaction with Keap1 (Kelch‐like ECH‐associated protein 1), which directs the transcription factor for proteasomal degradation. Phytochemicals are also good activators of the Nfr2 activity , and this ability makes phytochemicals able to prevent cell ageing‐related disorders . In this sense, the indirect antioxidant activity of natural products resulting in the production cytoprotective proteins (phase 2 enzymes) and endogenous direct antioxidants seems to be more important than their direct antioxidant activity.…”
Section: Selected Medicinal Plants With Active Anti‐ageing Propertiesmentioning
confidence: 99%